2021
DOI: 10.1016/j.bbrep.2021.101073
|View full text |Cite
|
Sign up to set email alerts
|

D- and l-amino acid concentrations in culture broth of Lactobacillus are highly dependent on the phylogenetic group of Lactobacillus

Abstract: d -amino acids produced by Lactobacillus are thought to contribute to the taste quality and health functions; however, no studies have comprehensively evaluated the concentrations of the D- and L-forms of amino acids separately in individual Lactobacillus strains. To gain insight into amino acid concentrations in Lactobacillus , we evaluated amino acid concentrations in culture broth of Lactobacillus separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…These results suggested that the fermentation using Lactobacilli increased their anti-melanogenic and anti-inflammatory effects. Based on the studies showing that Lactobacilli can use and produce amino acids [ 75 , 89 , 90 ] and polysaccharides [ 91 , 92 ], and the fact that maca root consists of various components, our results imply that during fermentation, Lactobacilli may change the components contained in maca root, causing a reduction in NO in macrophages and melanin in melanocytes. Therefore, further studies are needed to study which components of maca root extract change through fermentation.…”
Section: Discussionmentioning
confidence: 71%
“…These results suggested that the fermentation using Lactobacilli increased their anti-melanogenic and anti-inflammatory effects. Based on the studies showing that Lactobacilli can use and produce amino acids [ 75 , 89 , 90 ] and polysaccharides [ 91 , 92 ], and the fact that maca root consists of various components, our results imply that during fermentation, Lactobacilli may change the components contained in maca root, causing a reduction in NO in macrophages and melanin in melanocytes. Therefore, further studies are needed to study which components of maca root extract change through fermentation.…”
Section: Discussionmentioning
confidence: 71%
“…The results of this study are consistent with those of Fang et al [30], who reported that Lactobacillus was significantly positively correlated with the various flavor compounds (including lactic acid, acetic acid, ethyl ester, dodecanoic acid, and 2,4-di-tert-butylphenol) produced during the fermentation of Zhejiang rose vinegar. Furthermore, Lactobacillus has been reported to produce D-amino acids, which can enhance the taste of fermented foods [37]. Enterobacter exhibited a significant positive correlation with some esters with high odor activity.…”
Section: Pearson Correlation Analysis Between Core Microorganisms And...mentioning
confidence: 99%
“…The liquid of brown rice was diluted 1.67 times with water and sterilized at 95 • C for 15 min. For assuming industrial incubation, we used static condition, which was used in previous study (Sugahara et al, 2021). The precultures of MRSc broth were inoculated with 5% v/v into a saccharified liquid of brown rice.…”
Section: Sample Collection Using a Saccharified Liquid Of Ricementioning
confidence: 99%